Working With Veterans And Military Families Through Service Learning - Ann Byers
Veterans and military families have a wealth of stories and history to offer students and certain needs that can be filled by energetic, engaged, and caring young people. This type of service learning helps students put their history and social studies education into context. This book presents service learning with many examples of how students can use it to get to know and learn from local veterans while also giving back to them and providing assistance to a segment of the population that has served our national interests and now requires our assistance and support.